Audit Sistem Informasi Perpustakan Menggunakan Cobit 5.0 Domain Deliver, Service, and Support - Adelia Sakinah Rahmah; Dani Almansah; Dian Fahriza Syafitri; Diva Auliad; Wulan Indah Lestari (CV. ITTC INDONESIA, 2024)
This research aims to audit the North Sumatra State Islamic University (UINSU) library information system using the COBIT 5 framework, focusing on the Deliver, Service, and Support (DSS) domain. The audit process emphasizes Manage Operations (DSS01), Manage Service Requests and Incidents (DSS02), Manage Problems (DSS03), and Manage Continuity (DSS04). The audit results show that the capability level in the DSS domain has reached level 4 (predictable process), with a GAP of 1.60 from the expected level. The recommendations provided include increasing awareness and promoting the benefits of library websites, further optimization in handling service requests and incidents, evaluating menus and information searches, as well as improving visual design and display consistency. Implementation of these recommendations is expected to increase the level of capability of the UINSU library and provide better services to its users.